Análisis de cambio de coberturas mediante el uso de Google Earth Engine e imágenes Landsat en el Lago de Tota en el departamento de Boyacá (2023)
The rapid development of human beings has generated consequences in the environment, therefore, research has begun to identify and solve such problems. In recent years, the body of wáter of Lago de Tota has been affected by the overexploitation in the area of activities such as agriculture and fish farming, this work aims to identify the coverage in different years in order to quantify these changes that this area has suffered, for this purpose the Google Earth Engine tool was used through the Code Editor that allows generating scripts to perform this type of analysis.